Mechanisms of Practice-Related Reductions of Dual-Task Interference with Simple Tasks: Data and Theory - Strobach, Tilo (Adv Cogn Psychol, 2017)
In dual-task situations, interference between two simultaneous tasks impairs performance. With practice, however, this impairment can be reduced. To identify mechanisms leading to a practice-related improvement in sensorimotor dual tasks, the present review applied the following general hypothesis: Sources that impair dual-task performance at the beginning of practice are associated with mechanisms for the reduction of dual-task impairment at the end of practice. The following types of processes provide sources for the occurrence of this impairment: (a) capacity-limited processes within the component tasks, such as response-selection or motor response stages, and (b) cognitive control processes independent of these tasks and thus operating outside of component-task performance. Dual-task practice studies show that, under very specific conditions, capacity-limited processes within the component tasks are automatized with practice, reducing the interference between two simultaneous tasks. Further, there is evidence that response-selection stages are shortened with practice. Thus, capacity limitations at these stages are sources for dual-task costs at the beginning of practice and are overcome with practice. However, there is no evidence demonstrating the existence of practice-related mechanisms associated with capacity-limited motor-response stages. Further, during practice, there is an acquisition of executive control skills for an improved allocation of limited attention resources to two tasks as well as some evidence supporting the assumption of improved task coordination. These latter mechanisms are associated with sources of dual-task interference operating outside of component task performance at the beginning of practice and also contribute to the reduction of dual-task interference at its end.